WORLD FINANCIAL CENTERS ARE SOURCES OF ECONOMIC GROWTH (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the study of theoretical aspects of the functioning and characteristics of financial centers in modern conditions. International financial centers are key platforms of the global financial system, where mechanisms for attracting and managing capital flows from all over the world are built. The article provides an overview of approaches to defining the concept of “international financial center”, common in foreign and domestic academic literature.Considerable attention is paid to the analysis of approaches to considering IFCs as a function of a global city, and the consideration of the characteristic features of IFCs at the present stage of development is based on the analysis of methodological data from the GFC Global Financial Centers Index, which is compiled by the London analytical center Z/Yen Group Limited.